Charitable choices : religion, race, and poverty in the post welfare era - Bartkowski, John P., 1966- (New York University, 2003)
Congregations and faith-based organizations have become key participants in America's welfare revolution. Recent legislation has expanded the social welfare role of religious communities, thus revealing a pervasive lack of faith in purely economic responses to poverty. Charitable Choices is an ethnographic study of faith-based poverty relief in 30 congregations in the rural south. Drawing on in-depth interviews and fieldwork in Mississippi faith communities, it examines how religious conviction and racial dynamics shape congregational benevolence. Mississippi has long had the nation's highest.